Implementing open innovation concept in social business - Anna Svirina; Alfia Zabbarova; Karine Oganisjana (Journal of Open Innovation: Technology, Market, and Complexity, 2016)
Social business is an emerging concept which requires additional research especially in terms of priority management tools that can be used. The paper aims to evaluate how closed and open innovation concepts are implemented by social enterprises in the emerging information economy. The paper also studies social enterprises from the point of view of joint efficiency and innovation development concept evaluation to define best practices used by social entrepreneurs nowadays. The paper provides comparative analysis of two types of social business models: the ones based on open innovation and the ones based on formal closed innovative process. Research question is to estimate how implementation of open innovation influences social businesses' outcomes, and to define the way open innovation influences social enterprises' efficiency.
Keywords: 650; Open innovation; Social business; Business model Innovation process; Quantum economics